The Fornes Frame : Contemporary Latina Playwrights and the Legacy of Maria Irene Fornes - García-Romero, Anne (Book collections on Project MUSE., 2016)
"The book is an examination of the works of five contemporary Latina playwrights: Cusi Cram, Quiara Alegría Hudes, Elaine Romero, Caridad Svich, and Karen Zacarias. It argues that the playwright Maria Irene Fornes's writing and teaching have influenced the analyzed dramatists to produce plays that are more transcultural than previous generations of Latina playwrights"--Provided by publisher.